Infusing geriatrics expertise in health professions education through interprofessional faculty development. Issue 3 (3rd July 2022) - Marrs, Sarah A.; Ansello, Edward F.; Slattum, Patricia W.; Davis, Kimberly; Parsons, Pamela L.; Zimmerman, Kristin; Coogle, Constance L.
ABSTRACT: As the population of older adults continues to grow, the need for health care professionals trained in the delivery of interprofessional care for older adult patients is critical. The purpose of this paper is to detail the outcomes of an interprofessional, geriatrics training program for healthcare professionals with a faculty appointment. Specifically, we gathered outcomes at four levels: reactions/satisfaction, learning, behavioral, and organizational. Our findings suggest that programs structured like the Faculty Development Program (FDP) have the potential to increase the amount of geriatrics content introduced in already existing health professions curricula, as well as to offer faculty needed training in how to provide their students with interprofessional learning experiences.